Regional policy in EFTA industrial mobility : an examination of industrial mobility in the context of regional policies in EFTA countries - European Free Trade Association; Warne, E. J. D. (Geneva : Secretariat of the European Free Trade Association ; Washington : distributed in the U.S. by EFTA Information Office], 1971)
This is the report of an European Free Trade Association (EFTA) Economic Development Committee working party under the chairmanship of E. J. D. Warne focused on regional industrial development.
the report of an EFTA Economic Development Committee working party under the chairmanship of E. J. D. Warne
lje 10/04/2018
Loans
Keywords: Industrial location; Industrial promotion; Industrial mobility; Regional policy